2007
DOI: 10.1016/j.devcel.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Is Essential for Ventricular Chamber Development

Abstract: Ventricular chamber morphogenesis, first manifested by trabeculae formation, is crucial for cardiac function and embryonic viability and depends on cellular interactions between the endocardium and myocardium. We show that ventricular Notch1 activity is highest at presumptive trabecular endocardium. RBPJk and Notch1 mutants show impaired trabeculation and marker expression, attenuated EphrinB2, NRG1, and BMP10 expression and signaling, and decreased myocardial proliferation. Functional and molecular analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
502
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(548 citation statements)
references
References 52 publications
37
502
2
7
Order By: Relevance
“…S5). These defects are very similar to the phenotypes of Notch1 and Notch target RBPJk knockout mice (Timmerman et al, 2004;Limbourg et al, 2005;Grego-Bessa et al, 2007), supporting the idea that ADAM10 plays an essential role in the Notch pathway in regulating cardiac development.…”
Section: Impaired Emt and Ventricular Trabeculation In The Heart Of Asupporting
confidence: 70%
See 1 more Smart Citation
“…S5). These defects are very similar to the phenotypes of Notch1 and Notch target RBPJk knockout mice (Timmerman et al, 2004;Limbourg et al, 2005;Grego-Bessa et al, 2007), supporting the idea that ADAM10 plays an essential role in the Notch pathway in regulating cardiac development.…”
Section: Impaired Emt and Ventricular Trabeculation In The Heart Of Asupporting
confidence: 70%
“…Our investigation of Adam10 endothelial knockout mouse model explicitly demonstrates that Adam10 is essential for endocardial cushion formation, ventricular trabeculation, and vasculogenesis. The AEKO mice not only phenocopied the Notch1 and Notch targets knockouts (Krebs et al, 2000;Fischer et al, 2004;Timmerman et al, 2004;Limbourg et al, 2005;Grego-Bessa et al, 2007), but also showed downregulated expression of Notch target gene Snail and Bmp2 in the cardiac tissues. Because we delete Adam10 primarily in the endothelial cells, which are only small fraction of the total cardiac, the expression changes of Snail and Bmp2 could be more severe in Adam10 deficient endocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Bmp10 results in ventricular trabeculation defect due to decreased cardiomyocyte proliferation. Ablation of NOTCH signaling causes reduced Bmp10 expression and cardiomyocyte proliferation in the heart (36). Based on RNA in situ hybridization, there was no difference in Bmp10 expression in the trabeculae of the Zfp57 −/+ (M − Z + ) and −/− mz (M − Z − ) E10.5 embryos (SI Appendix, Fig.…”
Section: Notch Signaling Pathway Was Perturbed In the Heart Of Zfp57mentioning
confidence: 99%
“…Ablation of NOTCH signaling causes reduced BMP10 signaling and decreased cardiomyocyte proliferation (36). To determine if cardiomyocyte proliferation was reduced without ZFP57, we performed EdU incorporation assay in the heart of E13.5 embryos (Fig.…”
Section: Notch Signaling Pathway Was Perturbed In the Heart Of Zfp57mentioning
confidence: 99%
“…Loss of Notch1 leads to defects in angiogenesis, loss of cellularization in the AVC, blocked ventricular trabeculation, and disrupted vasculature resulting in embryonic lethality at E10.5 similar to Rbpj null mice [144,156,157]. Notch1 −/− mice have collapsed endocardium and lack cushion mesenchyme at the onset of valve formation, indicating that Notch1 is required for EMT [144].…”
Section: Notch Signalling In Cardiac Valve Developmentmentioning
confidence: 99%